Cover Feature: A Versatile Compact Parahydrogen Membrane Reactor (ChemPhysChem 24/2021). Issue 24 (13th December 2021) - TomHon, Patrick M.; Han, Suyong; Lehmkuhl, Sören; Appelt, Stephan; Chekmenev, Eduard Y.; Abolhasani, Milad; Theis, Thomas
Abstract : The Cover Feature illustrates a Spin Transfer Automated Reactor (STAR), which produces a continuous stream of nuclear spin hyperpolarization. In the STAR, parahydrogen diffuses through a semi‐permeable membrane to hyperpolarize small molecules in solution, including the antibiotic drug metronidazole and the metabolite pyruvate. The STAR also produces parahydrogen pumped RASER (Radiofrequency Amplification by Stimulated Emission of Radiation), creating everlasting NMR signal. More information can be found in the article by Patrick M. TomHon, Thomas Theis and co‐workers .